Acidic cultivation of Haematococcus pluvialis for improved astaxanthin production in the presence of a lethal fungus. (April 2019) - Hwang, Sung-Won; Choi, Hong Il; Sim, Sang Jun
Graphical abstract: Highlights: Acidic cultivation of H. pluvialis is effective in P. sedebokerensis suppression. Initial pH 4 was chosen to achieve contamination control and proper cell growth. Contamination may be inhibited due to denaturation of a host-recognition lectin. Stress relief strategies enhanced the astaxanthin titer by 104.8%. Astaxanthin titer was thus upgraded 141-fold compared to contaminated H. pluvialis . Abstract: An acidic cultivation strategy was developed to prevent contamination of a lethal fungus Paraphysoderma sedebokerensis in Haematococcus pluvialis culture for astaxanthin production. Instead of generally used neutral pH, an acidic condition (pH 4) was applied to the cultivation, resulting in a significant inhibition of the fungal contamination. This could be ascribed to the acidity-associated denaturation of a surface protein of P. sedebokerensis, which plays an important role in recognition of H. pluvialis . Stress relief strategies including stepwise light irradiation and naturally occurring nitrogen deficiency were employed in the induction stage to minimize the reduction of astaxanthin production caused by acidic pH. Accordingly, an astaxanthin titer of 84.8 mg L −1 was obtained, which is 141-fold of that from the completely contaminated culture and double of that without the stress relief methods. This strategy provides a persistent contamination control method that can be used for practical astaxanthin production by H. pluvialis .